2021
DOI: 10.1016/j.ihj.2020.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, safety and outcomes of left bundle branch pacing in octogenarians

Abstract: Objectives Left bundle branch pacing (LBBP) provides physiological pacing at low and stable threshold. The safety and efficacy of LBBP in elderly population is unknown. Our study was designed to assess the safety, efficacy and electrophysiological parameters of LBBP in octogenarian (≥80 years) population. Results LBBP was successful in 10 out of 11 patients. Mean age 82.1 ± 2.5 yrs. Follow up duration 7.7 months(range4–10). Indication for pacing included atrioventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 22 , 25 , 26 Similar case reports 27 , 28 also showed that in patients with heart failure who received LBBAP, their NYHA function grade improved along with cardiac parameters. Shunmuga et al 29 found that in patients older than 80, LBBAP can be used as an effective alternative therapy for CRT to improve cardiac function. Margarida 30 reported that LBBAP could correct the cardiac electromechanical dyssynchronization and ameliorate mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 25 , 26 Similar case reports 27 , 28 also showed that in patients with heart failure who received LBBAP, their NYHA function grade improved along with cardiac parameters. Shunmuga et al 29 found that in patients older than 80, LBBAP can be used as an effective alternative therapy for CRT to improve cardiac function. Margarida 30 reported that LBBAP could correct the cardiac electromechanical dyssynchronization and ameliorate mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Shunmuga et al 29 found that in patients older than 80, LBBAP can be used as an effective alternative therapy for CRT to improve cardiac function. Margarida 30 reported that LBBAP could correct the cardiac electromechanical dyssynchronization and ameliorate mitral regurgitation.…”
Section: Bnp and 6wmdmentioning
confidence: 99%